PROFITABILITAS, PELUANG PERTUMBUHAN, MODAL KERJA BERSIH SERTA DAMPAKNYA TERHADAP KEBIJAKAN PENAHANAN KAS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azimah Dianah; Ana Fitria; Abrar Amri; Rina Desiana (Jurnal Ekonomi Regional Unimal, 2019)
This research tests the effect of profitability, growth opportunity, and net working capital on corporate cash holding for a sample of banks company listed in Indonesian Stock Exchange over the period 2013-2015. Population of this research is 31 banks companies at the Indonesian Stock Exchange. This research use path analysis method. Hypothesis test of this research employs standardized multiple regression analysis. The result show that simultaneously profitablity, growth opportunity, and net working capital have influence enough to cash holding. While partially profitability has a positive influence enough to cash holding, growth opportunity and net working capital has a very weak negative effect on cash holding.